2010
DOI: 10.2460/javma.237.12.1395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a postexposure rabies prophylaxis protocol for domestic animals in Texas: 2000–2009

Abstract: The Texas PEP protocol was used during the 10-year period. Results indicated that an effective PEP protocol for unvaccinated domestic animals exposed to rabies was immediate vaccination against rabies, a strict isolation period of 90 days, and administration of booster vaccinations during the third and eighth weeks of the isolation period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…RABV is capable of immune subterfuge via decreasing or delaying the immune response or evading the immune system completely (27,28). Previous studies have demonstrated that the ability to avert the immune system is not equivalent among RABV variants (4,6,8,9).…”
Section: Discussionmentioning
confidence: 99%
“…RABV is capable of immune subterfuge via decreasing or delaying the immune response or evading the immune system completely (27,28). Previous studies have demonstrated that the ability to avert the immune system is not equivalent among RABV variants (4,6,8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the optimal dosage of SYN023 will be a balance between extending ideal neutralizing capacities to multiple lyssaviruses while minimizing vaccine interference concomitantly during human PEP. In addition, although all domestic species at risk should receive pre-exposure vaccination, based upon the considerable protection demonstrated in a highly relevant animal model, the use of MAbs for prophylaxis in veterinary medicine for management of the naïve individual should be further explored within a One Health context [31].…”
Section: Discussionmentioning
confidence: 99%
“…Post‐exposure vaccination of domestic animals with rabies vaccine during the preclinical period may prevent the development of clinical disease by preventing local viral replication and neuronal transmission. In the USA between 2000 and 2009, 1014 animals received PEP against RABV, without any failures recorded …”
Section: Discussionmentioning
confidence: 99%